Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(2^x.2^2.2^2=2^3\Rightarrow2^{x+2+2}=2^3\Rightarrow x+4=3\Rightarrow x=-1\)-1
\(\left(5^2+3^2\right).x+\left(5^2-3^2\right).x-40.x=10^2\)
\(\Rightarrow x.\left(5^2+3^2+5^2-3^2-40\right)=10^2\)
\(\Rightarrow x.\left(2.5^2-40\right)=10^2\)
\(\Rightarrow x.10=10^2\Rightarrow x=10^2:10\Rightarrow x=10\)
Đặt \(A=\frac{3}{5.8}+\frac{3}{8.11}+\frac{3}{11.14}+...+\frac{3}{32.35}\)
\(A=\frac{1}{5}-\frac{1}{8}+\frac{1}{8}-\frac{1}{11}+\frac{1}{11}-\frac{1}{14}+...+\frac{1}{32}-\frac{1}{35}\)
\(A=\frac{1}{5}-\frac{1}{35}=\frac{6}{35}\)
\(\Rightarrow x+\frac{6}{35}=-\frac{2}{7}\Rightarrow x=-\frac{2}{7}-\frac{6}{35}=-\frac{16}{35}\)
Dat A=3/5.8 +3/8.11 +.........+3/32.35
A=1/5-1/8+1/8-1/11+1/11-1/14+.............+1/32-1/35
A=1/5-1/35
A=6/35
=>x+6/35=-29/35
=>x=-29/35-6/35
=>x=-1
a: -x+5/9=-1/3
nên x=5/9+1/3=5/9+3/9=8/9
b: \(\Leftrightarrow\dfrac{1}{5}+\dfrac{1}{10}+\dfrac{11}{15}< x< \dfrac{1}{2}+\dfrac{13}{12}+\dfrac{1}{3}\)
=>31/30<x<23/12
mà x là số nguyên
nên \(x\in\varnothing\)
c: x+5/3=1/81
nên x=1/81-135/81=-134/81
x - ( 81 + 5x ) = 19
=> x - 81 - 5x = 19
=> ( x - 5x ) - 81 = 19
=> -4x = 19 + 81
=> -4x = 100
=> x = 100 : ( -4 )
=> x = -25
2x - ( 8 + 3x ) = 92
=> 2x - 8 - 3x = 92
=> ( 2x - 3x ) = 8 + 92
=> -x = 100
=> x = -100
\(x.x.x^2=81\)
\(\Leftrightarrow x^4=81\)
\(\Leftrightarrow\orbr{\begin{cases}x^4=3^4\\x^4=\left(-3\right)^4\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=3\\x=-3\end{cases}}\)
Vậy ..